Pengaruh Penambahan Plastik High Density Polyetilene (HDPE) dalam Campuran Hot Rolled Sheet Wearing Course (HRS-WC) terhadap Parameter Marshall, Kuat Tekan dan Kuat Tarik Belah - Akmus, Pepi Nega (Semesta Teknika, 2013)
In this study, plastics High-Density Polyethylene (HDPE) were used as an additional ingredient of asphalt for HRS-WC mixtures by using a variation of the plastic content of 0%, 2%, 4%, 6% to the asphalt weight. Bitumen content obtained from the optimum bitumen content of 7.5%. The purpose of this research is to examine and to compare the Marshall characteristics, compressive strength and split tensile of HRS-WC mixture. The results showed that the addition of HDPE plastic provide a significant influence on the marshall characteristic, split tensile strength and compressive strength. Asphalt stability with the addition of HDPE by 2%, 4% and 6% compliant with the specifications of marshall stability results respectively amounted to 2589.40 kg, 2257.13 kg and 2385.16 kg.